Katekese Tentang Program Pastoral Ekonomi Berkelanjutan Kepada Umat Stasi Mocok di Paroki Santo Arnoldus Janssen, Ponggeok - Stanislaus Efodius Harmansi; Imelda Sanjung (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Ruteng Diocese has launched 2023 as a sustainable economic pastoral year. As part of the Ruteng Diocese, the Saint Arnold Janssen Ponggeok Parish has the obligation to socialize sustainable economic pastoral programs to the people through catechesis in each Basic Ecclesial Community (BEC) in March and April 2023. This obligation is rather difficult to carry out because the number of catechesis facilitators is limited. The number of BECs is more than the number of facilitators. To overcome this problem, the Community Service Team (Pengabdian kepada Masyarakat, PkM) of the Theological Education Study Program of the Indonesian Catholic University of Santu Paulus Ruteng offered assistance. The selected location is Mocok Station. This station has 14 BECs. The PkM team functions as facilitators in each BEC. The activity was carried out twice in March 2023. This community service aims to inform the Ruteng Diocese's sustainable economic pastoral programs to the people of Mocok Station and stimulate their commitment to the success of the programs. The method used was 3M, namely, to look at (Melihat) the social reality of the people, to evaluate (Menilai) the reality in the light of the Word of God, and to plan actions (Merencanakan) to respond to the reality that the Word of God has enlightened. As a result, people understood the importance of utilizing the natural resources they have and the need to build work ethics in order to have a better quality of life. In addition, the people expressed their intention to be involved in the Ruteng Diocese's sustainable economic pastoral program. They succeeded in formulating and deciding on a concrete action plan that was in line with the aim to increase the people’s wellbeing in each BEC.